Mixed reviews on diversity initiatives: toward an institutional change model for Black faculty in engineering and computing - Miles, Monica L.; McGee, Ebony O.; Botchway, Portia (Frontiers in Education, 2024)
Introduction Universities across the United States have implemented initiatives to enhance diversity in science, technology, engineering, and mathematics (STEM) fields, focusing on improving outcomes for racially minoritized students. While many diversity initiatives target undergraduate programs, there is a gap in support for STEM graduate students. Recognizing the persistent underrepresentation of racially diverse populations in STEM, the Biden-Harris Administration launched the “Raise the Bar: STEM Excellence for All Students” initiative, aiming to bolster STEM education nationwide. Foundations like the Sloan Foundation have developed pathways programs for STEM students, extending support into graduate school and the professoriate. The success of diversity initiatives often hinges on the participation and endorsement of underrepresented STEM faculty. Methods This study investigates the perspectives of twenty-nine Black engineering and computing faculty regarding diversity initiatives within their respective departments. Grounded theory methodology guided the qualitative analysis, enabling a deeper understanding of the racialized diversity management framework. Drawing on institutional racism perspectives, the study aimed to develop a theoretical framework elucidating institutional engagement with and implementation of diversity initiatives in engineering education. Results The participants’ perspectives on diversity initiatives reflected features of organizational change. Three types of organizational environments emerged: 1) stagnant, characterized by aspirational commitments to diversity; 2) moderate, where underrepresented populations are recruited but expected to assimilate into the dominant culture; and 3) transformational, representing organizations taking significant steps towards creating equitable environments. The narratives of the study participants shed light on the varying effectiveness of efforts to increase the representation of successful Black students and faculty in engineering academia. Discussion The findings underscore the importance of understanding organizational contexts and dynamics in shaping the outcomes of diversity initiatives. By delineating the racialized diversity management framework, this study provides insights into the complexities of institutional engagement with diversity in engineering education. Addressing the challenges identified, particularly in environments characterized as stagnant or moderate, is crucial for advancing equity and inclusion in STEM fields. Effective diversity initiatives must go beyond recruitment efforts to create transformative, equitable environments conducive to the success of racially minoritized students and faculty in engineering academia.